Studi Tingkat Kenyamanan Pedestrian (Jalur Pejalan Kaki) di Pusat Kota Bandung: Studi Kasus Jalan Asia Afrika - Saepurrahman, Dewa (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2025)
Pedestrian pathways are crucial in urban transportation as they promote active mobility and enhance environmental quality. This study assesses the comfort of Bandung City's central pedestrian pathways, considering their physical state, supporting facilities, safety. This research investigates their interaction with the environment by employing field observations, user surveys, and quantitative and qualitative descriptive analyses. The findings reveal that several areas exhibit low levels of pedestrian comfort due to narrow pathways, uneven surfaces, and a lack of protection from weather conditions and motor vehicles. Recommendations for improvement focus on enhancing the physical quality of pedestrian routes, reorganizing pedestrian spaces, and integrating them with more inclusive public spaces. This study is expected to be a foundation for formulating policies to develop more comfortable and sustainable pedestrian infrastructure.